2005
DOI: 10.1128/aem.71.8.4487-4496.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Genetically Tractable Photoautotrophic Fe(II)-Oxidizing Bacterium, Rhodopseudomonas palustris Strain TIE-1

Abstract: We report the isolation and characterization of a phototrophic ferrous iron [Fe(II)]-oxidizing bacterium named TIE-1 that differs from other Fe(II)-oxidizing phototrophs in that it is genetically tractable. Under anaerobic conditions, TIE-1 grows photoautotrophically with Fe(II), H 2 , or thiosulfate as the electron donor and photoheterotrophically with a variety of organic carbon sources. TIE-1 also grows chemoheterotrophically in the dark. This isolate appears to be a new strain of the purple nonsulfur bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
210
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(216 citation statements)
references
References 63 publications
6
210
0
Order By: Relevance
“…(CARN5), as it may be observed in already sequenced related bacteria (http://www.genoscope.cns.fr/agc/microscope/ carnoulescope). In Rhodopseudomonas palustris strain TIE-1, a CobS-like protein has been previously shown to be involved in iron oxidation, but the mechanism remains unclear (Jiao et al, 2005). Interestingly, we showed that cobalamin strongly activates iron oxidation in At.…”
Section: Discussionsupporting
confidence: 49%
“…(CARN5), as it may be observed in already sequenced related bacteria (http://www.genoscope.cns.fr/agc/microscope/ carnoulescope). In Rhodopseudomonas palustris strain TIE-1, a CobS-like protein has been previously shown to be involved in iron oxidation, but the mechanism remains unclear (Jiao et al, 2005). Interestingly, we showed that cobalamin strongly activates iron oxidation in At.…”
Section: Discussionsupporting
confidence: 49%
“…It has also been reported that conductive minerals, such as magnetite, abundantly exist on the present and ancient Earth (14). Furthermore, reports have documented that dissimilatory iron-oxidizing and iron-reducing microbes generate crystalline iron-oxide nanoparticles as a result of respiration (28,32). We, therefore, consider that microbes have evolved biomolecular machineries for discharging electrons to and accepting them from mineral particles around their cells, resulting in IETs via electric currents.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these are the same as those found from primary sources. A notable exception is iron oxides, which form as a product of anoxygenic photosynthesis with Fe 2C as the electron donor (Widdel et al 1993;Heising et al 1999;Jiao et al 2005).…”
Section: Early Energy and Possible Community Structurementioning
confidence: 99%